Pasquale Stanislao Mancini's Principle of Nationality in the Argentine Science of International Law Between 19th and 20th Centuries: Peer-reviewed article (Italian Review of Legal History, 2022)
The principle of nationality proclaimed by Pasquale Stanislao Mancini in the prolusion of 1851 is one of the many attempts of legal sciences of the nineteenth century to respond to political characters of a specific historical context. This same principle is examined in the pages of the Argentine science of international law in the decades that followed in different ways, amid enthusiastic applause and fierce criticism. The purpose of this article is to carry out the reconstruction of the path followed by Mancini’s proposal in the debates of Argentine doctrine, between authors both in favor and against, emphasizing the main motivations that led, later during the twentieth century, to its complete rejection and consequent historicization. The hypothesis presented here is that the process of delegitimization and historicization of the Principle in Argentina took place mainly thanks to the peculiarities of the historical formation of this state reality, very distant from those experienced in the constitution of European States such as Italy, ‘cradle’ and at the same time inspiration of the Mancinian proposal.
Keywords: Pasquale Stanislao Mancini; Principle of nationality; Argentinian legal science; Science of the International Law